2018
DOI: 10.3389/fmicb.2018.00584
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution and Assemblages of Planktonic Fungi in the Coastal Waters of the Bohai Sea

Abstract: Fungi play a critical role in the nutrient cycling and ecological function in terrestrial and freshwater ecosystems. Yet, many ecological aspects of their counterparts in coastal ecosystems remain largely elusive. Using high-throughput sequencing, quantitative PCR, and environmental data analyses, we studied the spatiotemporal changes in the abundance and diversity of planktonic fungi and their abiotic and biotic interactions in the coastal waters of three transects along the Bohai Sea. A total of 4362 ITS OTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 74 publications
7
37
2
Order By: Relevance
“…Nevertheless, Chytrids was found to dominate Arctic marine fungal communities and might change primary production patterns rapidly with increased light penetration through the Arctic Ocean (Hassett and Gradinger 2016 ). In marine habitats, Chytridiomycota, Mortierellomycota, and Mucoromycota have been characterised as decomposers of pollens and leaves (Phuphumirat et al 2016 ) or pathogens of marine algae and animals (Scholz et al 2016 ; Wang et al 2018 ). These discoveries suggest that these fungi played a wide array of ecological roles potentially in the marine environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Chytrids was found to dominate Arctic marine fungal communities and might change primary production patterns rapidly with increased light penetration through the Arctic Ocean (Hassett and Gradinger 2016 ). In marine habitats, Chytridiomycota, Mortierellomycota, and Mucoromycota have been characterised as decomposers of pollens and leaves (Phuphumirat et al 2016 ) or pathogens of marine algae and animals (Scholz et al 2016 ; Wang et al 2018 ). These discoveries suggest that these fungi played a wide array of ecological roles potentially in the marine environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our present knowledge of deep-sea fungal diversity is largely based on the identification of the fruiting body, culturing surveys and conventional sequencing of the internal transcribed spacer (ITS) of rRNA gene clones (RaghuKumar et al 2004 ; Bass et al 2007 ; Nagano et al 2010 ; Singh et al 2011 , 2012 ; Xu et al 2014 , 2016 ; Zhang et al 2016 ). High-throughput sequencing (HTS) of DNA amplification from marine environments is a powerful approach for screening fungal communities with better capacity for detecting rare species, the taxa that present only as vegetative mycelia and cannot be cultured (Zhang et al 2016 ; Nagano et al 2017 ; Wang et al 2018 ; Xu et al 2018b ). A few of studies have been conducted to detect fungal assemblages present in bathypelagic and abyssopelagic zones and other specialised deep environments including hydrothermal systems, methane-dominated regions, and deep subsurface sediments (Bass et al 2007 ; Lai et al 2007 ; Takeshita et al 2007 ; Jebaraj and Raghukumar 2009 ; Le Calvez et al 2009 ; Nagano et al 2010 ; Nagahama et al 2011 ; Singh et al 2011 , 2012 ; Thaler et al 2012 ; Xu et al 2014 , 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Later, some of these unknown basal fungal lineages reported from deep-sea environments were affiliated within a novel fungal phylum, Cryptomycota (Jones et al 2011 ) and NCLC (Novel-Chytrid-Like-Clade) groups (Richards et al 2015 ). The presence of Cryptomycota and unknown basal fungal lineages, such as NCLC are more recognised and have been reported in recent years from many environments, including land, freshwater, sea ice, shallow to deep marine, with more extensive reporting from aquatic environments (both fresh and marine) (Jones et al 2011 ; Lazarus and James 2015 ; Ishii et al 2015 ; Richards et al 2015 ; Comeau et al 2016 ; Hassett and Gradinger 2016 ; Picard 2017 ; Rojas-Jimenez et al 2017 ; Wang et al 2018 ; Lepere et al 2019 ). Picard ( 2017 ) reported that marine benthic sediments harboured high proportion of novel sequences, which were assigned to early-diverging fungal groups and could not be assigned beyond phylum with statistical support, suggesting they belong to unknown lineages.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, culture-dependent and molecular techniques have allowed us to describe a large number of fungal taxa in seawater [ 33 , 34 ]. Likewise, fungi have been identified in several polar environments [ 35 , 36 , 37 ].…”
Section: Fungal Diversity and Ecology In Antarctic Marine Environmentsmentioning
confidence: 99%